An 18-country analysis of the effectiveness of five front-of-pack nutrition labels. (March 2023) - Pettigrew, Simone; Jongenelis, Michelle I.; Jones, Alexandra; Hercberg, Serge; Julia, Chantal
Highlights: Different front-of-pack food labels have varying ability to assist consumers. Coloured, spectrum labels were found to be of most assistance in 18 countries. These labels were best at identifying both the healthiest and least healthy options. Colour appears to be a critical element of effective front-of-pack nutrition labels. Abstract: Various front-of-pack food labels (FoPLs) are being introduced across the world, and discussion continues about the most effective label formats to improve consumers' (i) understanding of the relative healthiness of alternative products and (ii) product choices. Of increasing interest is the relative ability of different types of labels to steer consumers away from unhealthy options (aversion) versus steer them towards healthier options (attraction). The aim of this study was to assess aversion and attraction outcomes for five FoPLs (Health Star Rating, Multiple Traffic Lights, Nutri-Score, Reference Intakes, and Warning Label) across 18 countries (n = 18393). Descriptive analyses assessed improvements in consumer understanding and choice outcomes for each label across three different types of food products. Binary logistic regressions were used to compare the relative ability of the labels to improve respondents' understanding of product healthiness and their product choices, using the industry-developed Reference Intakes as the comparator. Aversion and attraction effects were assessed for each label/food type combination. Across the total sample, the Nutri-Score performed best in terms of both attraction and aversion results for understanding and simulated choice outcomes, followed by the Multiple Traffic Lights. The Reference Intakes exhibited the weakest performance overall, with the Warning Label and Health Star Rating falling in between. The most effective FoPLs featured a colour-coded spectrum design. The results indicate that front-of-pack labels that are effective in guiding consumers towards healthier food products can also be effective in steering them away from unhealthy options.